2011
DOI: 10.1098/rspb.2010.2368
|View full text |Cite
|
Sign up to set email alerts
|

A small increase in UV-B increases the susceptibility of tadpoles to predation

Abstract: Increased ultraviolet-B (UV-B) radiation as a consequence of ozone depletion is one of the many potential drivers of ongoing global amphibian declines. Both alone and in combination with other environmental stressors, UV-B is known to have detrimental effects on the early life stages of amphibians, but our understanding of the fitness consequences of these effects remains superficial. We examined the independent and interactive effects of UV-B and predatory chemical cues (PCC) on a suite of traits of Limnodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 64 publications
5
20
1
1
Order By: Relevance
“…Larvae in the UV+ treatments were exposed to 4.7±1.5 μW cm −2 of UV-B for 13 h per day with an additional peak of 36±4 μW cm −2 for 5 h occurring in the middle of the day. Replicating ambient UV-B levels has been shown to be lethal for the tadpoles of some species (van Uitregt et al, 2007), and so UV-B levels were ~6% of ambient radiation to enable us to investigate non-lethal effects (Alton et al, 2012;Alton et al, 2010) while maintaining sufficient survival rates (Alton et al, 2011;van Uitregt et al, 2007). Tadpoles in the UV-treatment were exposed to the same lighting regime generated by generic linear fluorescent bulbs (UV-B 8.5±1.5 μW cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Larvae in the UV+ treatments were exposed to 4.7±1.5 μW cm −2 of UV-B for 13 h per day with an additional peak of 36±4 μW cm −2 for 5 h occurring in the middle of the day. Replicating ambient UV-B levels has been shown to be lethal for the tadpoles of some species (van Uitregt et al, 2007), and so UV-B levels were ~6% of ambient radiation to enable us to investigate non-lethal effects (Alton et al, 2012;Alton et al, 2010) while maintaining sufficient survival rates (Alton et al, 2011;van Uitregt et al, 2007). Tadpoles in the UV-treatment were exposed to the same lighting regime generated by generic linear fluorescent bulbs (UV-B 8.5±1.5 μW cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have measured correlates of fitness such as locomotor performance [59], anti-predator morphology and behaviour [60], and age and size at metamorphosis [61], and have demonstrated that these are negatively impacted by exposure to UVR [62][63][64][65]. Only two studies that we know of have used predation trials to determine that exposure to increased UVR increases the susceptibility of tadpoles to predation [66,67]. Romansic et al [67] attributed this increased susceptibility to predation to UVR-induced tail deformities that may have impaired tadpole swimming Xenopus laevis Artificial lamps [196] Limb and digit malformations Hypsiboas pulchellus Artificial lamps [69] Lithobates pipiens Ambient sunlight [185,186] Artificial lamps [58,200] Rana temporaria Artificial lamps [63] Jaw malformations Hypsiboas pulchellus Artificial lamps [69] Locomotion performance…”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…The military strategy of defoliation, whereby American forces dumped hundreds of thousands of tonnes of herbicides on forests in Vietnam in the 1960s and 1970s, has caused large-scale deforestation and pollution, the effects of which are still present today [22]. At a global scale, the increase in ultra-violet (UV) radiation as a result of hydrofluorocarbon release can affect ecosystems by disrupting different lifehistory stages of vulnerable species, and its effect may be compounded by other stressors such as pollution [23,24].…”
Section: Human Activity Modifies the Abiotic And Biotic Environmentsmentioning
confidence: 99%